The role(s) of community health workers in primary health care reform in Kerala, before and during the COVID 19 pandemic: a qualitative study - Sankar D, Hari; Joseph, Jaison; Benny, Gloria; Surendran, Surya; Sharma, Santosh Kumar; Nambiar, Devaki (Frontiers in Health Services, 2024)
medicines to patients during the COVID-19 lockdown. The community members mentioned positively the delivery of home visits, delivery of medicines, and emotional support offered by CHWs during the home delivery of medicines and emotional support offered by CHWs during pandemic period. CHWs also noted that the honorarium of INR 6000 (US$73) was inconsistent and very low for the volume of work done. Conclusion: CHWs in Kerala play a crucial role in primary care reforms and COVID-19 management. Despite their strong work ethic and close relationship with local self-governments, low and irregular wages remain the biggest challenge.Kerala CHWs have been an integral part of the primary care team in Kerala and played a major role in successfully implementing primary care reforms and also managing the COVID-19 pandemic. The strong work ethic and close relationship with local selfgovernments in Kerala have helped CHWs gain greater acceptance and recognition in the communities they serve. Low and irregular wages continue to remain the biggest challenge faced by the CHWs in the state, which warrants policy response.